In-vitro ANTIBACTERIAL ACTIVITY OF EXTRACTS OF BITTER GOURD WITH SELECTED MEDIA - KUMARI and T.N.V.K.V. PRASAD, FLORA-GLAD CHIZOBA EKEZIE, JESSIE SUNEETHA, W, K. UMA MAHESWARI, B. ANILA (The Journal of Research, PJTSAU, 2019)
In recent years, there has been enormous interest in the development of anti-microbial agents from natural sources due to diseases caused by microbes which is on rampage causing large number of issues such as food poisoning, intestinal and extra intestinal infections, urinary tract infections, meningitis, peritonitis, mastitis, septicemia and gramnegative pneumonia. More recently, Multiple Drug Resistance (MDR) has developed due to indiscriminate use of commercial antimicrobial drugs commonly used in the treatment of such infectious diseases. Adding to this problem, antibiotics are sometimes associated with adverse effects on the host, including hypersensitivity, immune suppression and allergic response (Dey et al., 2010).